Malay Riau Ornamentation on Characters Building in Elementary School Students - Guslinda, Guslinda (Proceedings of the UR International Conference on Educational Sciences, 2018)
Malay Riau ornamentation as part of culture is not only seen as beauty but also has treasures. The treasure of Riau Malay ornamentation is found in the values and meanings inherent in its motives. As for the purpose of this study to describe the treasures of Riau decorative motifs as the planting of character values for elementary school students. The method in this study uses qualitative methods that describe and analyze the attitudes and perceptions of fourth grade elementary school students and using interviews and observations. From the results of the research, students can understand the values of the Malay ornamentation, this is because in the daily lives of the children, the names of the motifs of ornament are made and also introduced and instilled the values contained in the motif. Planters of these values are also carried out in the community by inviting children to participate in cultural activities such as money. Therefore, in this study, it can be concluded that the Riau Malay ornamental treasures can be used as the planting of character values to elementary school students.